2016
DOI: 10.1039/c6cc07321b
|View full text |Cite
|
Sign up to set email alerts
|

A drug-loaded nanoscale metal–organic framework with a tumor targeting agent for highly effective hepatoma therapy

Abstract: Drug delivery systems with targeting agents for precise drug release in cancer therapy are very significant and important. Herein, we report the rational design and synthesis of a DOX (doxorubicin) loaded UiO-68-type of nanoscale metal-organic framework (NMOF) with a tumor targeting agent (folic acid, FA), DOX@UiO-68-FA (3), as a multifunctional drug delivery system for hepatoma (Hep G2) therapy via tail-vein injection. Compared to free DOX, FA-unloaded DOX@Mi-UiO-68 (2), 3 exhibits a much higher antitumor eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Importantly, nanoscale MOFs have much higher anticancer efficacy in in vivo studies. 180 The zeolite imidazolate framework (ZIF-8) has been used as biocompatible MOFs for co-delivery of an anticancer drug (DOX) and a P-glycoprotein inhibitor of verapamil hydrochloride (VER) to overcome MDR and deliver an active targeting drug. The resulting design was further modied by PEG-FA to obtain better stability and active targeting ability.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…Importantly, nanoscale MOFs have much higher anticancer efficacy in in vivo studies. 180 The zeolite imidazolate framework (ZIF-8) has been used as biocompatible MOFs for co-delivery of an anticancer drug (DOX) and a P-glycoprotein inhibitor of verapamil hydrochloride (VER) to overcome MDR and deliver an active targeting drug. The resulting design was further modied by PEG-FA to obtain better stability and active targeting ability.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…This multifunctional nanomedicine was used for efficient hepatoma therapy by intravenous injection. They further confirmed that the as‐synthesized nanoscale MOFs perform a much higher anticancer efficacy in in vivo studies . MOFs could be also coated by exosomes for the efficient loading and sealing of drugs.…”
Section: Mofs For Drug Delivery and Chemotherapymentioning
confidence: 56%
“…For example, Jihye and coworkers used folic acid to modify TCPP@PCN-224 which improved the efficacy of the original nano drug delivery system [56]. Same as above, folic acid was modified by Li et al on a metal organic framework to get FA/DOX@UiO-68 [57]. They injected different substances into the tail vein of liver cancer mice.…”
Section: Active Targeted Therapy Based On Metal Organic Frameworkmentioning
confidence: 99%